Chemical structure changes of lacustrine Type-II kerogen under semi-open pyrolysis as investigated by solid-state 13C NMR and FT-IR spectroscopy. (June 2020) - Hou, Lianhua; Ma, Weijiao; Luo, Xia; Tao, Shizhen; Guan, Ping; Liu, Jinzhong
Abstract: At present, there is a lack of research on the structural changes of lacustrine Type-II kerogen, which is regionally distributed but has significant potential for hydrocarbon resources. In our previous work, a series of non-hydrous, temperature-based semi-open pyrolysis experiments have been performed on the Chang 7 oil shale to simulate the thermal maturation (from 0.53 %Ro to 1.68 %Ro) of lacustrine Type-II kerogen. In that work, the parallel reaction pathway for kerogen decomposition was supported. The aim of this work is to reveal the structural changes of the post-pyrolysis kerogen. Integrated analysis including elemental analysis, programmed pyrolysis (Rock-Eval), Fourier transform infrared (FT-IR) spectroscopy, and solid-state 13 C nuclear magnetic resonance ( 13 C NMR) spectroscopy were conducted on the native unheated and post-pyrolysis rocks and kerogens. Based on the compositional features of the hydrocarbon products, structural changes of the post-pyrolysis kerogen were investigated, and insights on the initial chemical structure of the kerogen were also obtained. Before the peak hydrocarbon-generating stage ( R o < 0.6%), defunctionalization of oxygen-containing functional groups, which leads to the generation of water, CO2 and NSOs, occurs simultaneously with the detachment of short aliphatic side chains and small aromatic rings, which leads to the generation of volatile fractions (C6 –C14, C15+ sat and C15+ aro). This process suggests that the Chang7 kerogen is highly branched. During the peak hydrocarbon-generating stage (0.6–1.09 % R o ), the concurrent breakage of weak cross-link bonds and long aliphatic chains lead to the simultaneous peak generation of liquid hydrocarbons and NSOs. This reflects the highly cross-linked features of the Chang7 kerogen. After the peak hydrocarbon-generating stage ( R o > 1.09%), the reactions in the previous two stages produce a highly aromatic kerogen. The increased aromaticity of the highly matured kerogen is most likely to be caused by aromatization or dehydrogenation of hydroaromatics and coking of aromatic bitumen, not by fusing or condensation of aromatic rings. Highlights: Chemical structural evolution of Chang7 lacustrine Type-II kerogen was characterized for the first time. Kerogen reached artificial maturation under non-hydrous, temperature-based semi-open pyrolysis experiments. Parallel bond breaking mechanism of unusual lacustrine Type-II kerogen was supported from chemical structure changes.